If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(2x + -2) = 8 + -3x Reorder the terms: 8 + -1(-2 + 2x) = 8 + -3x 8 + (-2 * -1 + 2x * -1) = 8 + -3x 8 + (2 + -2x) = 8 + -3x Combine like terms: 8 + 2 = 10 10 + -2x = 8 + -3x Solving 10 + -2x = 8 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 10 + -2x + 3x = 8 + -3x + 3x Combine like terms: -2x + 3x = 1x 10 + 1x = 8 + -3x + 3x Combine like terms: -3x + 3x = 0 10 + 1x = 8 + 0 10 + 1x = 8 Add '-10' to each side of the equation. 10 + -10 + 1x = 8 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 8 + -10 1x = 8 + -10 Combine like terms: 8 + -10 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| (2u^2/3)/(6u^3/5) | | F+42=78 | | (-1/3)y-(2/5)=1/2 | | 64a^3-1a=0 | | 6-(4y-4)=6-5y | | -2(-8-7x)=142 | | (9/4)-(1/2)v=(-1/2) | | 6(2+x)=5(x-3) | | 12m+5+m=44 | | V+20=62 | | a/7/a/26 | | (-5/2)=(3/5)v-(5/3) | | 25/9x^2-50/3x | | (5x+4)(3x^2-17x+10)=0 | | 6(-3x+4)=-84 | | 6v^2-13v-28=0 | | x+5x=65 | | 4w-6=6 | | -7.9=v/3-3.1 | | 5/9*(5-32) | | 4=(-5/9)+v | | 6x-4=5x-4 | | 8=-4+x/-3 | | u+(3/4)=-3/8 | | 2(9+x)=32 | | n-6=30 | | w+(3/5)=(1/3) | | X+3=7x+15 | | 4u+3u=35 | | 5x-3=4x-2 | | r/15=0 | | k+35=106 |